FEATURES OF MAINTENANCE OF THE ROADWAY CEMENT CONCRETE DURING THE SUMMER BUILDING PERIOD - Rudenko, M. M.; Doronina, V. O. (Science and Transport Progress, 2009)
In the article the analysis of efficiency of methods of maintenance of road concrete in a summer period of placing is presented. The technology of maintenance of fresh-placed road cement-concrete is related to the complex of measures aimed at obtaining the 28-day’s strength, which would be equal or exceeding the strength of concrete at hardening in normal moisturizing conditions. There are described the methods of curing the fresh-placed concrete with the use of different protective covers, the of which is of favorable temperature-moisture conditions for hardening of concrete and growth of strength, as well as obtaining of the and long-operable pavement.